The information-seeking behaviour of paediatricians accessing web-based resources. Issue 8 (12th May 2009) - Prendiville, T W; Saunders, J; Fitzsimons, J
Abstract : Objectives: To establish the information-seeking behaviours of paediatricians in answering every-day clinical queries. Design: A questionnaire was distributed to every hospital-based paediatrician (paediatric registrar and consultant) working in Ireland. Results: The study received 156 completed questionnaires, a 66.1% response. 67% of paediatricians utilised the internet as their first "port of call" when looking to answer a medical question. 85% believe that web-based resources have improved medical practice, with 88% reporting web-based resources are essential for medical practice today. 93.5% of paediatricians believe attempting to answer clinical questions as they arise is an important component in practising evidence-based medicine. 54% of all paediatricians have recommended websites to parents or patients. 75.5% of paediatricians report finding it difficult to keep up-to-date with new information relevant to their practice. Conclusions: Web-based paediatric resources are of increasing significance in day-to-day clinical practice. Many paediatricians now believe that the quality of patient care depends on it. Information technology resources play a key role in helping physicians to deliver, in a time-efficient manner, solutions to clinical queries at the point of care.